The Effectiveness of Substitution Drill in Teaching Simple Present Tense - Yos Hendar Ambasalu; Raisa Anakotta; Ari Wibowo (TEKILA: Journal of Language Teaching and Literature, 2024)
Simple present tense is the most useful tense in English since it is often used in daily life to express habits or regular activities and to talk about facts. Aware of this, the researcher decided to apply substitution drill to teach simple present tense at the eleventh grade of MA Emeyodere Kota Sorong to find out whether the substitution drill technique is effective or not in teaching simple present tense. The design of this research is one group pretest-posttest. The population of this research is the students of MA Emeyodere Kota Sorong with the total of 38 students. Based on the convenience sampling, the researcher chose the eleventh grade with the total of 14 students, but only 7 students involved as the sample from this class in this research. The results of this research show that there is a significant difference in students’ average score in pretest and posttest. The students’ average score before using the substitution drill (pretest) is 35.71. whereas the students’ average score after using the substitution drill (posttest) is 75. Meanwhile, the N-gain’s result is 61.11 or 61% interpreted as quite effective. It means that the alternative hypothesis (Ha) is accepted. So, the conclusion is that the substitution drill technique is effective for teaching simple present tense.